The feasibility of re-enacting the Export Support Fund Act in Iraq - الحديثي, صلاح الدين حامد; سالم, سالم عبد الحسين (Journal of Economics and Administrative Sciences, 2011)
Economists agree upon the importance of exports and their positive impacts on the economic variables. Therefore، they studied policies encouraging exports and set out the instrumentalities supporting them. These instrumentalities included a combination of fiscal، monetary، commercial، production policies like the tax policy that is encouraging to the exports، exchange rates reduction، establishing commercial free zones، better production quality، fostering investment climate، and preparation of the necessary financing before the exporting process and afterwards.This research is interested in the finding aspect amongst the instrumentalities encouraging exports which is parallel to the objective of the research to know the benefit of activating the operation of Export Promotion Fund in Iraq. Thus، this fund is identified: its establishment، objectives، ways of funding and procedures of operation as a basis to go ahead in the details of research. Also، we have touched upon the international experiments in the field of funding and promoting exports in a summarized way in a number  of developing countries that have made good accomplishments in this field like China، India، South Korea and Egypt to show the importance of exports in practice.The research reached to two types of results:The first relates to the organizational structure of the Fund which، in short، provides financial support only، without the other aspects of support. This financial support is directed to Iraqi goods exported، but not to the exporters. Also، it does not provide funding for export productions and does not provide guarantees and insurance against risks for exports. Furthermore، the resources of finance this fund has already dried out because of suspending the instructions or modifying them.The second relates to the environment surrounding the work of the Fund: it is found out that the infrastructure of the Iraqi economy does not support the domestic competitive production and does not help attract the foreign investment in addition to the out-of-date industrial and agricultural production methods.Taking all the above into consideration، the research reaches the result of the weakness of activating the Export Promotion Fund in Iraq which has been de-activated since 1991 for being quite improper in its tasks، resources and management with the improvement achieved in Iraq.Thus، the research recommends that work should be done to establish a new legal framework for a new Exports Promotion Fund or Import/Export Bank that takes into consideration the difficulties that face Iraqi exports and the international experiments in this field and the international developments in the field of commercial relationships focusing on the funding aspects.